Yeo-Johnson 변환을 통한 비대칭 GARCH 모형 - 정환식(Hwan Sik Jung); 조신섭(Sinsup Cho); 여인권(In-Kwon Yeo) (Ŭngyong tʻonggye yŏnʼgu, 2024)
In this paper, we introduce an extended GARCH model designed to address asymmetric leverage effects. The variance in the standard GARCH model is composed of past conditional variances and past squared residuals. However, it is not possible to model asymmetric leverage effects with squared residuals alone, so in this paper, we propose a new extended GARCH model to explain the leverage effects using the Yeo-Johnson transformation which adjusts transformation parameter to make asymmetric data more normal or symmetric. We utilize the reverse properties of Yeo-Johnson transformation to model asymmetric volatility. We investigate the characteristics of the proposed model and parameter estimation. We also explore how to derive forecasts and forecast intervals in the proposed model. We compare it with standard GARCH and other extended GARCH models that model asymmetric leverage effects through empirical data analysis. 이 논문에서는 비대칭 지렛대 효과를 처리하기 위한 확장된 GARCH 모형을 소개한다. 표준 GARCH 모형의 분산은 이전의 조건부 분산과 이전의 잔차 제곱 항으로 구성되어 있다. 잔차 제곱항으로는 비대칭 지렛대 효과를 모형화할 수 없는데 이 논문에서는 Yeo-Johnson 변환을 이용하여 지렛대 효과를 설명하는 확장된 GARCH 모형을 제안한다. Yeo-Johnson 변환은 변환 모수를 조절하여 비대칭 자료를 보다 정규성 또는 대칭성을 만족하도록 만든데 우리는 Yeo-Johnson 변환의 성질을 역으로 이용하여 비대칭 변동성을 모형화 한다. 제안 모형의 특징에 대해 살펴보고 모수 추정에 대해 알아본다. 제안 모형에서 예측과 예측구간을 어떻게 구하는지 살펴보고 실증 자료분석을 통해 제안모형과 GARCH, 비대칭 지렛대 효과를 모형화한 다른 GARCH 모형을 비교해 본다.